(untitled) (Journal of Parents and Teachers, 2025)
The article discusses the involvement of parents in the management of the school, emphasizing that they are directly responsible for their children’s education. However, they express that the work and social environment they live in prevents them from fulfilling this role, as they are unsure how to do it correctly and do not have the time that these actions require. Additionally, it addresses some specific problems currently present in education that need to be resolved.